Sanksi Pidana Terhadap Pelaku yang Melarikan Diri dari Karantina Kesehatan - I Made Anandha Ida Rusmantara; I Nyoman Gede Sugiartha; Kade Richa Mulyawati (Fakultas Hukum Universitas Warmadewa, 2022)
Coronavirus Disease 2019 or COVID-19 is a pandemic threat that has been legally established by the World Health Organization (WHO) because it has an impact on the survival of the population. So that the Government of Indonesia issued legal regulations as an effort to overcome one of their health quarantines but still not obeyed by the public in connection with this, how is the legal arrangement on health quarantine? And what are the legal sanctions against someone who is fleeing health quarantine? This research uses normative research methods. The basis of the Health Protection and Quarantine Law in the 1945 Constitution stipulates that a prosperous life is born and inner, living, and getting a good and healthy living environment and entitled to health services is a community right. Those who violate the legal regulations that have been imposed in this pandemic situation get verbal reprimands, written reprimands, and administrative sanctions.